Could Risk, Corporate Governance, and Corporate Ethics Enhance Social Performance ? Evidence from Islamic Banks in Indonesia - Mukhibad, Hasan; Setiawan, Doddy (Indian Journal of Finance, 2020)
This study sought to demonstrate empirically the relationship between the level of banks’ risk (measured by leverage, capital adequacy ratio (CAR) ; financing deposit ratio (FDR) ; non-performing financing (NPF), corporate governance mechanism, profitability, and Ethics Disclosure Index (EDI)) on their social performance. The sample was 11 Islamic commercial banks in Indonesia. The data used were secondary data compiled from financial and annual reports for the period from 2009-2017. The data were then processed using multivariate analysis and structural equation modeling with WarpPLS tool. The study demonstrated that banks’ social distribution activities were not used to control risk. The role of the Sharia Supervisory Board (SSB) was not found to be effective in improving banks’ social performance. Meanwhile, the role of independent commissioners was able to increase the distribution of qardh al-hassan (interest free loans) and distribution of qardh (interest free financing). The level of profitability was only able to increase zakah expenditure (religious donations) and EDI was proven empirically to have a positive influence on the distribution of zakah funds and qardh financing. Islamic banks are required to demonstrate performance in terms of social concerns that is well aligned with the achievement of financial performance. The social activities that are a part of the performance of Islamic banks are concrete evidence of bank participation in improving people's welfare, reducing poverty, and caring for the environment.